Психологічні особливості тривожності в юнацькому віці (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the problem of anxiety in adolescence. Some psychological determinants of anxiety of young men and women are identified and analyzed. The results of the diagnostic experiment on revealing the level of reactive and personality anxiety of young people are presented.
Keywords: anxiety; communication; disadaptation; frustration; emotional instability